Hidden economy and its scientific-theoretical foundations and socio-economic consequences. (Zien Journal of Social Sciences and Humanities, 2022)
This article is about the hidden economy and its scientific-theoretical foundations and socioeconomic consequences. General concepts about hidden economic situations are briefly explained.